Alterações na vegetação florestal nativa nas bacias hidrográficas dos lajeados São José e Passo dos Índios – oeste de Santa Catarina: efeitos hidrológicos e na perda de solos entre 1989 e 2015 - Otsuschi, Cristina (2017)
The research deals with the relation between remaining native forest vegetation and environmental functions in watersheds. The environmental functions chosen for this research are: flow rate, soil loss and surface runoff. Considering the population growth and urban expansion in ‘Chapecó’, it is important to have environmental planning in order to avoid compromising the environmental functions of the remaining native vegetation and also not to trigger environmental problems, such as deforestation, erosion and floods. In order to understand the effects of fragmentation and reduction of remaining native vegetation on the mentioned environmental functions, watersheds from slabs ‘São José’ and ‘Passo dos Índios’, located in the west region of Santa Catarina’s state, Brazil, were compared. ‘São José’ watershed is an intermunicipal waterway, having its headsprings in the municipalities of ‘Chapecó’ and ‘Cordilheira Alta’, while the slab of ‘Passo dos Índios’ has its headsprings in the municipality of ‘Chapecó’. ‘São José’ slab watershed is characterized by having areas with more fragments of remaining vegetation, many rural properties and being the watershed responsible for the city’s water supply. ‘Passo do Índios’ slab watershed can be considered urbanized, with several stretches of water courses channeled. In order to know the remaining native vegetation fragmentation process in the period from 1989 to 2015, the following maps were elaborated: a) land use in the years 1989, 1996, 2010 and 2015; b) 2015 simulation of the Permanent Preservation Areas (PPAs) according to the environmental laws; c) 2015 simulation of the replacement of remaining fragments by crop areas; and d) 2015 simulation of the replacement of remaining fragments by built-up areas. In order to understand the effects of vegetation fragmentation on the flow rates, soil loss and surface runoff, according to land use in different years and verify the possibility of using scenarios, for the environmental planning in the study area, the Soil and Water Assessment Tool - SWAT was used. For the simulation of scenarios the elements considered were: climatic data from 1985 to 2015; flow rates and river-level data, land-use maps, soil types map and the Digital Elevation Model. In order to learn the influence of the remaining native vegetation (land use) on the flow rate, surface runoff and soil loss reduction, it was decided to use the average rainfall from 1989 to 2015, and the average flow rate and soil loss, considering land use a variable. The study area was divided into 40 sub-basins for comparison purposes. The subbasins with the lowest flow rates, soil loss and surface runoff were the ones that had the highest rates of remaining native vegetation. The sub-basins of ‘São José’ slab would be more vulnerable to flow rates and soil loss, while the sub-basins of ‘Passo do Índios’ slab would have higher surface runoff rates. The PPA simulation highlighted the need for alternatives to increase areas with vegetation, reducing environmental problems such as floodings, rivers silting and erosion.